The use of antibiotics to improve phage detection and enumeration by the double-layer agar technique - Santos, Sílvio Roberto Branco (2009)
Background The Double-Layer Agar (DLA) technique is extensively used in phage research to enumerate and identify phages and to isolate mutants and new phages. Many phages form large and well-defined plaques that are easily observed so that they can be enumerated when plated by the DLA technique. However, some give rise to small and turbid plaques that are very difficult to detect and count. To overcome these problems, some authors have suggested the use of dyes to improve the contrast between the plaques and the turbid host lawns. It has been reported that some antibiotics stimulate bacteria to produce phages, resulting in an increase in final titer. Thus, antibiotics might contribute to increasing plaque size in solid media. Results Antibiotics with different mechanisms of action were tested for their ability to enhance plaque morphology without suppressing phage development. Some antibiotics increased the phage plaque surface by up to 50-fold. Conclusion This work presents a modification of the DLA technique that can be used routinely in the laboratory, leading to a more accurate enumeration of phages that would be difficult or even impossible otherwise.